Growing Up Down South: Spatial and Temporal Variability in Early Growth of Fuegian Sprat Sprattus fuegensis From the Southwest Atlantic Ocean - García Alonso, Virginia A.; Brown, Daniel R.; Pájaro, Marcelo; Capitanio, Fabiana L. (Frontiers in Marine Science, 2020)
The Fuegian sprat Sprattus fuegensis represents one of the most important pelagic resources in the Southwest Atlantic Ocean (SWAO), exerting a crucial ecological role as an intermediary link in Patagonian food webs. Otolith microstructure of 217 age-0 sprats were analyzed aiming to characterize growth patterns and possible environmental effects over them. Samples were gathered during three oceanographic surveys (spring 2014; autumns 2016, 2017) in Tierra del Fuego (TDF) and the Marine Protected Area Namuncurá-Burdwood Bank (MPAN-BB), the first Argentinian open-sea marine protected area. Daily growths (DG) of larvae and post-larvae were estimated by individually modeling size and otolith radius relationships through back-calculation procedures using potential and linear functions respectively. Increment widths (IW) and DG values and trajectories were assessed for older sprats (i.e. survivors) sampled in the autumn surveys considering the habitat, year sampled and sprats’ hatching seasons, and were additionally evaluated in relation to sea-surface temperature (SST). IW and DG trajectories differed primarily according to the habitat sampled and sprats’ hatching seasons. Overall, strong coupling was detected between IW and DG trajectories with SST in both habitats. However, statistical assessment on particular comparisons showed that this general trend is not strictly invariant. Even though several results pinpointed a positive correlation between IW and DG with SST, the highest DG were estimated for summer- and autumn-born sprats sampled in 2016 in the MPAN-BB, period and habitat with the lowest SST values. These results unveil a complex relationship between spatial and temporal variability during early growth of Fuegian sprats, supplying relevant information that could be used in the creation of adequate ecosystem based management strategies in the SWAO.